Peran Ayah Terhadap Pendidikan Anak dalam Keluarga Perspektif Al-Qur’an: Studi Tafsir Tarbawi Q.S Luqman: 14-19 - Raja Muhammad Kadri (Jurnal test, 2023)
The role of fathers in children's education in the family has received the spotlight because various studies have found that the high rate of father's disengagement in family education is found. In the discourse on children's education, it was found that most fathers consider children's education to be the duty and obligation of a wife. The role of the father is very important for the child's education and will have a negative impact on children who do not feel the role and involvement of the father in their education. The solution to this problem will be found in the Qur'an, namely by examining Q.S Luqman verses 13-19 which provides an overview of the important role of a father in educating his child. The type of research used in this research is library research with content analysis. This research is included in the category of qualitative research, which is to produce descriptive data in the form of words. In order to understand the verses of the Koran in this study, the Tarbawi interpretation style method was used. The results of the study show that there are three roles of the father in Q.S Luqman, namely: first, the role of the father in educating the child's faith in Q.S Luqman verses 13-19; second, the father's role in children's worship education in Q.S Luqman verses 13-19; third, the father's role in children's moral education in Q.S Luqman verses 13-19.